Pacing profiles and tactical behaviors of elite runners - Casado, A.; Hanley, B.; Jiménez-Reyes, P.; Renfree, A. (Journal of Sport and Health Science, 2021)
• Elite athletes` pacing behaviors differ depending on race distance and whether races longer than 800 m are conducted during championships or "meets." • Optimizing finishing position requires the adoption of a leading position with as much as a lap remaining in 1500 m and 5000 m championship races. • Staying within a pack of runners who follow a realistic, non-excessive pace from the beginning of major championship long-distance races is also recommended to optimize performance (finishing time).